2015
DOI: 10.1002/anie.201502041
|View full text |Cite
|
Sign up to set email alerts
|

Actinide‐Mediated Catalytic Addition of EH Bonds (E=N, P, S) to Carbodiimides, Isocyanates, and Isothiocyanates

Abstract: Unprecedented catalytic reactivity of actinide coordination complexes toward heterocumulenes, such as carbodiimides, isocyanates, and isothiocyanates is reported. The mono(imidazolin-2-iminato) thorium(IV) complex [Th(Im(Dipp) N){N(SiMe3 )2 }3 ] (1) was applied as a precatalyst for the addition of EH (E=N, P, S) bonds to the YCX core (Y=R2 N; X=NR2 , O, S) of carbodiimides, isocyanates, and isothiocyanates. The respective insertion products were obtained in high yields under mild reaction conditions, with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 44 publications
2
46
1
Order By: Relevance
“…Theh ydrophosphination of olefins and alkynes has received much attention in the last decade, [4] but the use of heterocumulene substrates has been less explored, with examples of precatalysts for these reactions being limited to rare-earth, [5] alkali-metal, [6] and group 2c omplexes. [7] The hydrophosphination of organic isocyanates,yielding phosphinocarboxamide products,islimited to afew recent examples, all of which are catalyzed by f-block complexes.…”
Section: Organophosphoruscompoundsareavitalclassofchemicalsmentioning
confidence: 99%
“…Theh ydrophosphination of olefins and alkynes has received much attention in the last decade, [4] but the use of heterocumulene substrates has been less explored, with examples of precatalysts for these reactions being limited to rare-earth, [5] alkali-metal, [6] and group 2c omplexes. [7] The hydrophosphination of organic isocyanates,yielding phosphinocarboxamide products,islimited to afew recent examples, all of which are catalyzed by f-block complexes.…”
Section: Organophosphoruscompoundsareavitalclassofchemicalsmentioning
confidence: 99%
“…Therefore this process has been widely studied over the past decade using lanthanide catalysts [100][101][102][103][104][105][106]. However, only recently Eisen et al, have reported the application of a thorium catalyst for this type of atom-economic catalytic transformation [107]. The mono(imidazolin-2-iminato) thorium (IV) complex [(Im Dipp N)Th(N(SiMe3)2)3] (15) was successfully applied as pre-catalyst for addition of aromatic and aliphatic amines, phosphines and thiols to carbodiimides, isocyanates and isothiocyanates, furnishing the respective addition products in moderate to high yields under mild reaction conditions.…”
Section: Insertion Of Nucleophilic E-h (E = N P S) Bonds Into Hetermentioning
confidence: 99%
“…Subsequent protonolysis by two equivalents of phosphine leads to the formation of the catalytically active thorium species C under generation of two equivalents of guanidine B. The insertion of two equivalents of carbodiimide into the Th-P bond intermediate C gives rise to the thorium bis(phosphaguanidine) compound D. The rate determining step of the reaction mechanism is the protonolysis reaction of D with two equivalents of phosphine, which furnishes the phosphaguanidine product E under regeneration of the active catalyst C (Scheme 26) [107]. Scheme 26.…”
Section: Insertion Of Nucleophilic E-h (E = N P S) Bonds Into Hetermentioning
confidence: 99%
See 1 more Smart Citation
“…Carbodiimides in particular have been shown to insert stoichiometrically into the actinide–carbon bond of Cp*2AnMe 2 (An = U, Th), giving rise to the corresponding pentamethylcyclopentadienyl–amidinate complexes of the early actinides, 51 however only in this year was the process made catalytic, mediated by a mono(imidazolin-2-iminato) thorium( iv ) complex and often accompanied by extended reaction times and moderate conversions. 52 Moreover, the low-yielding multi-step ligand synthesis provides a further challenge accompanying the production and application of this complex. Recently, we have shown that a series of simple amido–actinide complexes of the formula U[N(SiMe 3 ) 2 ] 3 ( 1 ) and [(Me 3 Si) 2 N] 2 An[κ 2 -( N , C )–CH 2 Si(CH 3 ) 2 N(SiMe 3 )] (An = U ( 2 ), Th ( 3 )) ( Fig.…”
Section: Introductionmentioning
confidence: 99%